The development of the Chinese version of the Sports Emotional Intelligence Scale - Zhang, Jia; Bai, Donghuan; Qin, Long; Song, Pengwei (Frontiers in Psychology, 2022)
Objective: To revise and test the Chinese version of the Sports Emotional Intelligence Scale (SEIS) in sports situations. Methods: After pretesting 112 college students, 832 college students were formally tested, and item analysis, validity test, internal consistency reliability analysis, and calibration validity and equivalence test of the Chinese version of the SEIS were performed. The Chinese version of the SEIS had 14 items with four dimensions (evaluation of others' emotions, self-emotional management, emotion use, and social skills), with a cumulative variance contribution of 57.812 percent; the four-factor measurement model fit well (2/df=3.743, NFI=0.917, GFI=0.945, AFGI=0.913, CFI=0.926, and RMSEA=0.062). The internal consistency coefficients (Cronbach's α) of the Chinese version of the SEIS ranged from 0.824 to 0. 905, and the split-half reliability ranged from 0.807 to 0.891; the correlations between the total SEIS score and its dimensional scores and the calibration variables were significantly correlated (p<0.05), ranging from 0.255 to 0.603. The gender measure equivalence test was valid, and the mean difference of potential variables across gender groups was not significant in the potential mean analysis. Conclusion: The Chinese version of the SEIS has good reliability and validity, andit it is appropriate for assessing emotional intelligence in sports situations.